Relationship between adipokines and androgens in children and young adults with congenital adrenal hyperplasia - Apsan, Jennifer; Lekarev, Oksana; Thomas, Charlene; Zhu, Yuan-Shan; Cohan, Kaela; Lin-Su, Karen (Frontiers in Endocrinology, 2024)
Children and young adults with congenital adrenal hyperplasia (CAH) are at increased risk of obesity and insulin resistance. There is evidence that children with CAH have increased visceral adiposity, which has been linked to metabolic syndrome and cardiovascular disease (CVD). The adipokine adiponectin has been shown to correlate with reduced metabolic risk, whereas the adipokines visfatin and leptin have been linked to visceral fat and adipocyte inflammation and can serve as biomarkers of increased metabolic risk. Few studies to date have characterized adipokine levels in children and young adults with congenital adrenal hyperplasia. We sought to investigate the relationship between adiponectin, leptin and visfatin levels to metabolic risk factors and androgen levels in children and young adults with CAH. Methods: Fasting blood was obtained for visfatin, leptin, adiponectin, glucose, insulin, CRP, lipid panel, total cholesterol (TC), triglycerides (TG) and HbA1c, as well as standard laboratory tests to assess adrenal control, from children with CAH due to 21-hydroxylase deficiency. HOMA-IR was calculated based on fasting glucose and insulin. Anthropomorphic measurements of BMI and waist-to-hip ratio were also obtained. Results: Adiponectin and androstenedione were inversely correlated (R = -0.57, p =0.016). There was a positive correlation between leptin and BMI percentile (R = 0.63, p <0.001) as well as leptin and HOMA-IR (R = 0.63, p <0.01). Glucocorticoid dose had a positive correlation with HOMA-IR (R=0.56, p = 0.021). Visfatin was inversely correlated with HDL cholesterol (R = -0.54, p = 0.026) and total cholesterol (R = -0.49, p <0.05). Overweight children and young adults had a significantly higher leptin (p = 0.02) and HOMA-IR (p=0.001) than non-overweight children and young adults. Conclusion: The inverse relationship between adiponectin and androstenedione suggests that better CAH control can reduce the risk of insulin resistance and metabolic syndrome. However, a high glucocorticoid dose appears to increase the risk of insulin resistance, underscoring the delicate balance required when treating CAH.